Ñāṉa vaḻi - Jayēntira Sarasvati, Jagatguru Sankaracharya of Kamakoti, 1934- (Vāṉati Patippakam, 1979)
Discourses on Hinduism by the head of the Kanchi Kamakoti Peetham, a Saivite religious institution.